Pro-poor land administration: Towards practical, coordinated, and scalable recording systems for all. (February 2019) - Hendriks, Bob; Zevenbergen, Jaap; Bennett, Rohan; Antonio, Danilo
Highlights: Pro-poor land recordation tool promotes land rights and improves access to land. Tool is positioned relative to other responsible land administration approaches. Further incorporation of foci on institutional, political economy, community aspects. Ten refined and one new design element and modification of graphical depiction tool. More research recommended on impact assessment and future alignment of approaches. Abstract: The global land community has increasingly recognized the need to work towards practical, coordinated integration and scalable implementation of alternative approaches to land administration, ones that better serve the interests of the majority of groups in society. The pro-poor land recordation tool (PPLRT) contains a set of design elements developed to improve protection and access to land for the poor, particularly women, youth and vulnerable groups, especially in areas with (rapidly) changing land use. Building on earlier PPLRT work, this article positions the PPLRT relative to other responsible land administration approaches (especially Fit-For-Purpose). It further develops the PPLRT design elements and system based on incorporating increased foci on institutional and political economy aspects and a more complex notion of community, stemming from four documented cases of records keeping, and expert feedback. The paper recommends refinement of all but one of the design elements, addition of a new design element, and modification of the PPLRT's graphical depiction. Recommended strategic areas for further research are: assessing the impacts of pro-poor land recordation on achievement of the SDGs (particularly land related indicator 1.4.2) and New Urban Agenda (particularly paragraph 35); identifying the necessary conditions for improved, coordinated, and scaled PPLRT implementation in various contexts; and articulation of the circumstances for effective future alignment, conversion and integration of land data collected by local communities with those of existing land administration agencies.